The effect of web‐based pediatric palliative care education on the palliative care knowledge level and practices of nursing students. - Akdeniz Kudubes, Aslı; Bektas, Murat (Perspectives in Psychiatric Care, 2020)
Purpose: This study is aimed to investigate the effect of web‐based pediatric palliative care education on nursing students' knowledge level and practices related to palliative care. Methods: The study was conducted with 265 nursing students including an intervention and a control group. The intervention group was given web‐based pediatric palliative care education. Findings: A statistically significant difference was found between the total and subscale pretest and posttest scores of the students in the intervention and control groups regarding the palliative care knowledge level and self‐reported palliative care practices. Practical Implications: The web‐based pediatric palliative care education is an effective training model for nursing students to improve palliative care knowledge level and practices of the students.